Host-Derived Artificial MicroRNA as an Alternative Method to Improve Soybean Resistance to Soybean Cyst Nematode - Tian, B.; Li, J. R.; Oakley, T. R.; Todd, Timothy C.; Trick, Harold N. (My University, 2016)
The soybean cyst nematode (SCN), Heterodera glycines, is one of the most important pests limiting soybean production worldwide. Novel approaches to managing this pest have focused on gene silencing of target nematode sequences using RNA interference (RNAi). With the discovery of endogenous microRNAs as a mode of gene regulation in plants, artificial microRNA (amiRNA) methods have become an alternative method for gene silencing, with the advantage that they can lead to more specific silencing of target genes than traditional RNAi vectors. To explore the application of amiRNAs for improving soybean resistance to SCN, three nematode genes (designated as J15, J20, and J23) were targeted using amiRNA vectors. The transgenic soybean hairy roots, transformed independently with these three amiRNA vectors, showed significant reductions in SCN population densities in bioassays. Expression of the targeted genes within SCN eggs were downregulated in populations feeding on transgenic hairy roots. Our results provide evidence that host-derived amiRNA methods have great potential to improve soybean resistance to SCN. This approach should also limit undesirable phenotypes associated with off-target effects, which is an important consideration for commercialization of transgenic crops.
Citation: Tian, B., Li, J. R., Oakley, T. R., Todd, T. C., & Trick, H. N. (2016). Host-Derived Artificial MicroRNA as an Alternative Method to Improve Soybean Resistance to Soybean Cyst Nematode. Genes, 7(12), 13. doi:10.3390/genes7120122
Citation: Tian, B., . . . & Trick, H. (2016). Host-Derived Artificial MicroRNA as an Alternative Method to Improve Soybean Resistance to Soybean Cyst Nematode. Genes, 7(12), 13. https://doi.org/10.3390/genes7120122
Keywords: Artificial Microrna; Soybean Cyst Nematode; Soybean; Resistance; Efficient Virus-Resistance; Heterodera-Glycines